MISI ISLAMISME DALAM TERJEMAH TAFSIRIYAH MUHAMMAD THALIB : Analisis Wacana Kritis Teun A. Van Dijk - Fuaddin, Achmad (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This paper contains the mission of Islamism wrapped in the translation of the Qur'an. Freedom of speech which began in the reform era in Indonesia caused mass organizations that voiced the ideology of their group's thoughts to appear in front of the public. Muhammad Talib came to the surface to voice his opinions by criticizing the government when it was deemed not in accordance with his understanding. One of Muhammad Talib's criticisms of the government was through the interpretation of the interpretation and his correction of the Ministry of Religion's translation. As chairman of the Indonesian Mujahidin Council (MMI), Talib often calls on the general public and general institutions such as the government to implement Islamic law. One of the efforts made is to guide the discourse of Islamism through his translation of the Qur'an. This paper includes library research using a discrete analysis methodology. While the approach (approach) used is critical discourse analysis socio-cognitive approach. Based on the analysis, it can be concluded that Muhammad Talib's translation of Tafsiriyah tends to direct the interpretation of the verses of the Qur'an according to his ideology, invites readers to always obey Islamic teachings and apply Islamic Shari'ah in their entirety in daily life and invites Muslims to be loyal to all forms of Islamic struggle. In addition, he also openly criticized the government system of Muslim countries which he thought were not in accordance with the Shari'ah that he understood.